Biomimicry as a Sustainable Design Methodology—Introducing the ‘Biomimicry for Sustainability’ Framework - Lazaara Ilieva; Isabella Ursano; Lamiita Traista; Birgitte Hoffmann; Hanaa Dahy (Biomimetics, 2022)
Biomimicry is an interdisciplinary approach to study and transfer principles or mechanisms from nature to solve design challenges, frequently differentiated from other design disciplines by its particular focus on and promise of sustainability. However, in the biomimicry and biologically inspired design literature, there are varying interpretations of how and whether biomimetic designs lead to sustainable outcomes and how sustainability, nature, and mimesis are conceptualised and engaged in practice. This paper takes a particular focus on the built environment and presents a theoretical overview of biomimicry literature spanning across specific fields, namely architecture, philosophy, sustainability and design. We develop upon conceptual considerations in an effort to contribute to the growing calls in the literature for more reflective discussions about the nuanced relationship between biomimicry and sustainability. We further develop a ‘Biomimicry for Sustainability’ framework that synthesises recent reflective deliberations, as a possible direction for further theorisation of biomimicry, aiming to elaborate on the role of biomimicry as a sustainable design methodology and its potential to cultivate more sustainable human–nature relations. The framework is used as a tool for retrospective analysis, based on literature of completed designs, and as a catalyst for biomimetic design thinking. The objective of this paper is to serve as a point of departure for more active and deeper discussions regarding future biomimetic practice in the context of sustainability and transformational change, particularly within the built environment.